Aberrant post‐translational modifications compromise human myosin motor function in old age. Issue 2 (2nd February 2015) - Li, Meishan; Ogilvie, Hannah; Ochala, Julien; Artemenko, Konstantin; Iwamoto, Hiroyuki; Yagi, Naoto; Bergquist, Jonas; Larsson, Lars
Summary Novel experimental methods, including a modified single fiber in vitro motility assay, X‐ray diffraction experiments, and mass spectrometry analyses, have been performed to unravel the molecular events underlying the aging‐related impairment in human skeletal muscle function at the motor protein level. The effects of old age on the function of specific myosin isoforms extracted from single human muscle fiber segments, demonstrated a significant slowing of motility speed (P < 0.001) in old age in both type I and IIa myosin heavy chain (MyHC) isoforms. The force‐generating capacity of the type I and IIa MyHC isoforms was, on the other hand, not affected by old age. Similar effects were also observed when the myosin molecules extracted from muscle fibers were exposed to oxidative stress. X‐ray diffraction experiments did not show any myofilament lattice spacing changes, but unraveled a more disordered filament organization in old age as shown by the greater widths of the 1, 0 equatorial reflections. Mass spectrometry (MS) analyses revealed eight age‐specific myosin post‐translational modifications (PTMs), in which two were located in the motor domain (carbonylation of Pro79 and Asn81) and six in the tail region (carbonylation of Asp900, Asp904, and Arg908; methylation of Glu1166; deamidation of Gln1164 and Asn1168). However, PTMs in the motor domain were only observed in the IIx MyHC isoform, suggesting PTMs in the rod region contributed to the observed disordering of myosin filaments and the slowing of motility speed. Hence, interventions that would specifically target these PTMs are warranted to reverse myosin dysfunction in old age.